FORMULASI SEDIAAN GEL NANOPARTIKEL LIPID EKSTRAK DAUN BI-NAHONG (Anredera cordifolia (Ten.) Steenis) - Dwiastuti, Rini; Ardiyati, Shinta Elvina (Sam Ratulangi University, 2020)
ABSTRACT Binahong leaf extract has low water solubility. To increase the solubility of binahong leaf extract, it is necessary to formulate lipid nanoparticle gel dosage form. Lipid nanoparticles are preparations that can deliver both hydrophilic and lipophilic drugs. This study aims to make a gel lipid nanoparticles from binahong leaf extract with the physical properties parameters of the gel preparation. This research is a experimental study with independent variables of the concentration of binahong extract and variables depending on the size of the lipid nanoparticles and the physical properties of the gel. Gel making was done by using a variation of the amount of extract 5% and 10%. Testing the physical properties of the gel includes organoleptic, viscosity, dispersibility, pH, homogeneity, and syneresis. The physical stability test carried out is accelerated stability test using the freeze thaw cycling method for 3 cycles. Based on the results of the PSA test, of the two formulas made, one formula fulfills the range 50-100 nm. After testing the physical properties of the gel, the two formulas had a dispersion capacity within the 3-5 cm range, were homogeneous, and did not occur syneresis. The results of the viscosity test showed that the two formulas did not meet the 20-30 Pa.s. The pH test results showed that the two formulas did not meet the pH range 4.5-6.5. Key word: binahong; lipid nanoparticle; soy lecithin, gel ABSTRAKEkstrak daun binahong memiliki kelarutan dalam air yang rendah. Untuk meningkatkan kelarutan ekstrak daun binahong, perlu dilakukan formulasi sediaan dalam bentuk gel nanopartikel lipid. Nanopartikel lipid merupakan sediaan yang dapat membawa obat hidrofilik maupun lipofilik. Penelitian ini bertujuan untuk membuat gel nanopartikel lipid ekstrak daun binahong yang memenuhi parameter sifat fisis sediaan gel. Penelitian ini merupakan eksperimental murni dengan variabel bebas konsentrasi ekstrak binahong dan variabel tergantung ukuran nanopartikel lipid dan sifat fisis gel. Pembuatan gel dilakukan dengan menggunakan variasi jumlah ekstrak 5% dan 10%. Pengujian sifat fisis gel meliputi organoleptis, viskositas, daya sebar, pH, homogenitas, dan sineresis.. Uji stabilitas fisis yang dilakukan adalah uji stabilitas dipercepat dengan metode freeze thaw cycling selama 3 siklus. Berdasarkan hasil uji PSA, dari dua formula yang dibuat, satu formula memenuhi rentang 50-100 nm. Setelah dilakukan uji sifat fisik gel, kedua formula memiliki daya sebar sesuai rentang 3-5 cm, homogen, dan tidak terjadi sineresis. Hasil uji viskositas menunjukkan kedua formula tidak memenuhi rentang 20-30 Pa.s. Hasil uji pH menunjukkan kedua formula tidak memenuhi rentang pH 4,5-6,5. Kata Kunci: binahong; nanopartikel lipid; soy lecithin, gel